Dates of transplantation and productivity of habanero pepper with drip irrigation - López López, Rutilo; Inzunza-Ibarra, Marco Antonio; Fierro-Álvarez, Andrés; Palma-López, David Jesús (Revista Mexicana de Ciencias Agrícolas, 2018)
The effect of the date of transplant on the production of habanero pepper and the efficient use of irrigation water (UEA) was quantified and the profitability of the production was determined under drip irrigation and plastic cover conditions. The work was carried out in the municipality of Huimanguillo, Tabasco in a Fluvisol eutric soil. The Orange variety was used in five transplant dates: 1) September 17, 2014, 2) September 30, 2014, 3) December 23, 2014, 4) January 10, 2015 and 5) February 12, 2015. Four validation plots were established in the PV-2016 cycle. The transplant was performed 45 days after emergence of the seedlings in trays, with a density of 13 400 plants ha-1. The irrigation was applied based on crop evapotranspiration (ETc=ET0 Kc) where the reference evapotranspiration (ET0) was estimated with the “A” type evaporimeter tank. The following culture coefficients (Kc) were used: 0.4, 0.8 and 0.7 in the initial, intermediate and final stages of crop development, respectively. It is concluded that the dates of transplantation from September 17 to February 12 have a similar effect on fruit yield except for the date of January 10, affected by Phytophthora capsici. As for the UEA, the date of transplantation of September 30 increased 16.5% with respect to February 12 and 33.7% with respect to January 10. The yield of the crop was higher on the dates of December and February, obtaining a cost benefit ratio of 3.1 and 3.5, respectively.